Permasalahan sosial dalam film black panther karya Ryan Coggler: Kajian sosiologi sastra - Jumardan, Sulis (Maliki Interdisciplinary Journal, 2024)
Social issues are problems or challenges that affect individuals or society as a whole, often involving inequality, injustice, or human rights violations. Various factors, including culture, economics, politics, and the environment, can contribute to social problems. This study aims to present the social problems found in the film Black Panther. This study uses a qualitative descriptive method. The data of this study are conversations, expressions, and ways of speaking in the film Black Panther. The data collection technique uses the technique of watching, listening and taking notes. Social problems in the Black Panther film are (1) Racism of white people towards black people. (2) Robbery. (3) Murder. (4) Power struggle.